A Student-Run Free Mental Health Clinic for the Immigrant and Refugee Population in Clarkston, Georgia - Celia Foster; Philip Polychroniou; Martha Ward; Ann Schwartz (Journal of Student-Run Clinics, 2019)
Immigrant and refugee populations have high rates of mental health diagnoses but typically access services at lower rates than the general population because of cultural and structural impediments. Comprehensive health care is essential for future societal success of this population. This article discusses the establishment of a monthly mental health clinic at a pre-existing health center catering primarily to refugee and immigrant populations. In addition to its primary goal of meeting a need for low-cost mental health services, a secondary goal was to provide medical students and psychiatry residents with an opportunity to treat diverse populations and thereby increase their ability to provide culturally sensitive care. This article outlines the clinic’s operations, to date, as well as successes and challenges faced.